RELEVANCE OF COMPETENCIES OF ECONOMIC EDUCATION GRADUATES IN THE ERA OF INDUSTRY 4.0: TRACER STUDY AND STAKEHOLDER PERSPECTIVES - Andi Emil Salim; Muhammad Rakib; Agussalim Agussalim (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2026)
The rapid development of the Industry 4.0 era demands that university graduates have competencies aligned with the needs of an increasingly dynamic and technology-based workforce. This study aims to analyze the relevance of the competencies of graduates of the Economics Education Undergraduate Program at Makassar State University for the 2015–2024 period from a tracer study and stakeholder perspective. The study used a quantitative descriptive approach involving 318 alumni and 15 stakeholders, including school principals. Data were collected through a structured questionnaire and analyzed using descriptive statistics and gap analysis. The results showed that the graduates' employment rate was relatively high and supported by practical and soft skills relevant to the demands of Industry 4.0. These findings emphasize the importance of aligning the curriculum with industry needs, enhancing practice-based learning, and strengthening collaboration with the business world and industry. This research is expected to be the basis for formulating curriculum development policies to increase the competitiveness and relevance of Economics Education graduates